1976
DOI: 10.1136/jmg.13.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of genetic disorders.

Abstract: Summary. Three hundred and fifty pregnancies were monitored by transabdominal amniocentesis in the fourteenth to sixteenth week of gestation followed by karyotyping or The safety and reliability of amniocentesis and the possible effects on the outcome of pregnancy are evaluated. Prenatal diagnosis offers a promising alternative for parents who are at risk of having a child with a genetic disease which can be detected in amniotic fluid or in cultured amniotic fluid cells.Since the first reports of fetal karyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…Colobomas and microphthalmia have not been seen in patients with familial 11;22 translocations who have inherited normal chromosomes 11 and 22 and the der(22) from the translocation carrier parent. Although colobomas and microphthalmia have also not been seen in other familial trisomies for 22pter-qll, they have been seen in familial trisomies for 22pter-q12 [Niermeijer et al, 1976;Al Saadi et al, 1977;Bendel et al, 19821, supporting a more distal localization of the genes responsible for these eye anomalies. It is not clear why S.K., whose duplication appears to extend into 22q12, has no eye abnormalities whereas the patient described by Reiss et al [19851, whose duplication extended only to 22q11.2, had bilateral colobomas.…”
Section: Discussionmentioning
confidence: 91%
“…Colobomas and microphthalmia have not been seen in patients with familial 11;22 translocations who have inherited normal chromosomes 11 and 22 and the der(22) from the translocation carrier parent. Although colobomas and microphthalmia have also not been seen in other familial trisomies for 22pter-qll, they have been seen in familial trisomies for 22pter-q12 [Niermeijer et al, 1976;Al Saadi et al, 1977;Bendel et al, 19821, supporting a more distal localization of the genes responsible for these eye anomalies. It is not clear why S.K., whose duplication appears to extend into 22q12, has no eye abnormalities whereas the patient described by Reiss et al [19851, whose duplication extended only to 22q11.2, had bilateral colobomas.…”
Section: Discussionmentioning
confidence: 91%
“…This figure was lower in those who needed only a single tap. Galjaard (1976) (also in Niermeijer et al, 1976) quotes lower failure rates based on an inquiry covering 46 centres in 8 countries in Western Europe and a much lower proportion of repeat taps (4 3 % against our 12%). We too find that dry taps or bloodstained fluid are the commonest causes of failure, followed, in order of importance, by failure to establish satisfactory cell cultures.…”
Section: Success Ratementioning
confidence: 84%
“…Of these three cases, one of the procedures was performed transvaginally due to placental location, one fetus was at risk for Pompe disease (showed deficiency of α-1,4-glucosidase activity), and one fetus was conceived by a mother with a balanced translocation (the fetal cells failed to grow and were not available for analysis). Based on these considerations and other analyses in the study, the authors concluded that the miscarriage risk associated with amniocentesis was ± 1% (Niermeijer, Sachs, Jahodova, Tichelaar-Klepper, Kleijer, & Galjaard, 1976).…”
Section: Miscarriage Risk Associated With Amniocentesismentioning
confidence: 83%